Community detoxification for alcohol dependence: A systematic review. (21st June 2016) - Nadkarni, Abhijit; Endsley, Paige; Bhatia, Urvita; Fuhr, Daniela C.; Noorani, Aneesa; Naik, Aresh; Murthy, Pratima; Velleman, Richard
Abstract: Issues: Despite the potential advantages of community detoxification for alcohol dependence, in many countries the available resources are mostly focused on specialist services that are resource‐intensive, and often difficult to access because of financial or geographical factors. The aim of this systematic review is to synthesise the existing literature about the management of alcohol detoxification in the community to examine its effectiveness, safety, acceptability and feasibility. Approach: The systematic review was guided by an a priori defined protocol consistent with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) statement. Cochrane library, Medline, EMBASE, PsycINFO, Global Health and CINAHL databases were searched using appropriate search terms. A qualitative synthesis of the data was conducted as the heterogeneity of study designs, samples and outcomes measured precluded a meta‐analyses. Key Findings: Twenty studies with a range of designs were eligible for the review. Community detoxification had high completion rates and was reported to be safe. Compared to patients undergoing facility based detoxification, those who underwent community detoxification had better drinking outcomes. Community detoxification was cheaper than facility based detoxification and generally had good acceptability by various stakeholders. Implications: For certain patients, community detoxification should be considered as a viable option to increase access to care. Conclusions: Although the current evidence base to some extent supports the case for community detoxification there is a need for more randomised controlled trials testing the cost effectiveness of community detoxification in comparison with inpatient detoxification. [Nadkarni A, Endsley P, Bhatia U, Fuhr DC, Noorani A, Naik A, Murthy P, Velleman R. Community detoxification for alcohol dependence: A systematic review Drug Alcohol Rev 2017;36:389–399]